Gendered Cosmology, Landscape and Species-Inclusive Community in Yunnan’s Tibeto-Burman Origin Myths - Tommaso Previato (International Quarterly for Asian Studies)
This paper examines gender- and species-inclusive notions of community as reflected in the origin myths, animistic beliefs and practices of a few Tibeto-Burman minorities in the uplands of China’s southwestern province of Yunnan. Among these minorities, culture-specific views of descent and cosmocentric attitudes toward sentient nature showcase women’s social standing and role in enhancing relational empathy with non-human actors or species, as well as with a pantheon of deities who are believed to (co)inhabit or own the physical landscape. Integrating sources of knowledge from environmental history, comparative mythology and anthropology, the paper presents a selection of case studies on the Mosuo, Naxi, Yi and other minority cultures, demonstrating how relations with multiple non-human selves can be genealogical and how rituals aimed at influencing them can have positive effects on community well-being.